High-throughput screening to predict highly active dual-atom catalysts for electrocatalytic reduction of nitrate to ammonia. (1st December 2022) - Rehman, Faisal; Kwon, Soonho; Musgrave, Charles B.; Tamtaji, Mohsen; Goddard, William A.; Luo, Zhengtang
Abstract: Ammonia is an essential chemical owing to its importance in fertilizer production and other industrial applications. Electrocatalytic nitrate reduction to ammonia (NO3 RR) holds great promise for low-temperature ammonia production while simultaneously addressing nitrate-based environmental concerns. To provide the mechanistic understanding needed to design an effective electrocatalyst, we systematically investigated the catalytic performance of metal-based dual-atom catalysts (DACs) anchored on two-dimensional (2D) expanded phthalocyanine (Pc) for NO3 RR. We found that NO3 RR can efficiently produce ammonia on Cr2 -Pc, V2 -Pc, Ti2 -Pc, and Mn2 -Pc surfaces with low limiting potentials of − 0.02, − 0.25, − 0.34, and − 0.41 VRHE, respectively. Moreover, using the free energy difference of *NO3 - and *H as a descriptor, we found that the hydrogen evolution reaction is significantly suppressed on the DAC surface due to an ensemble effect in which the two metal atoms cooperate to selectively form ammonia. We performed high-throughput screening to develop an efficient metal-based DAC for NO3 - reduction, followed by a mechanistic study to elucidate the NO3 RR pathway on the DAC. This work provides design information for advancing sustainable ammonia synthesis under ambient conditions. Graphical Abstract: ga1 Highlights: High-throughput in silico screening of metal-based dual-atom catalyst for the electrochemical nitrate reduction to ammonia. Cr2 -Pc, V2 -PC, Ti2 -Pc, and Mn2 -Pc are all predicted to have outstanding electrochemical performance for ammonia synthesis. Dual metal atoms embedded in two-dimensional phthalocyanine strongly suppress the competing hydrogen evolution reaction.